Land Use - Turner, Christian; Open Textbook Library (Open Textbook Library, 2014)
This text explores the laws governing the use of land. Sometimes narrowly focused, often intensely local, land use regulation may give the impression of a highly specialized field with small stakes. The text is divided into three parts: First, we will survey the ordinary, local administrative scheme of land use regulation. The cases in this section are intended to establish what that system is and what it's standards are. In the second part of the course, we will turn our attention to cases illustrating litigation attacks on the ordinary administrative scheme. The purpose here is not, as it was in the first part, to understand better the standards the administrators should apply, but to understand the constraints imposed on the contents of local laws, the procedures of enactment and permitting, and the composition of local lawmaking bodies. In the third part, we focus on the distributive concerns raised by land use regulation. The regulatory takings doctrine has gone from, literally, nothing, to wrestling to disentangle distributive concerns from substantive ones, to trying to craft either rules or standards to identify regulations that go "too far" and should be considered "takings" within the meaning of the Fifth Amendment. We will consider what the doctrine's purposes are, how it should be governed, and how it should be invoked as a procedural matter.
1. Preface2. The Zoning System -- 2.1. Introduction -- 2.2. Variances -- 2.3. Special Use Permits -- 2.4. Comprehensive Planning -- 3. Judicial Review -- 3.1. Substantive Due Process -- 3.2. Adjudication and Quasi-Adjudication -- 3.3. Procedure -- 3.4. Discriminatory Zoning -- 3.5. Anticompetitive Zoning -- 3.6. Spot Zoning -- 3.7. Contract Zoning -- 3.8. Nonconforming Uses -- 3.9. Vested Rights -- 3.10. Neighbor Consent Provisions -- 4. Regulatory Takings -- 4.1. Origins -- 4.2. Theory -- 4.3. Doctrine -- 4.4. Procedural Issues -- 4.5. Exactions -- 4.6. German Takings Law
In English.
Description based on print resource
Keywords: Law -- Textbooks -- United States; Property Law -- Textbooks